2016
DOI: 10.1128/aac.00265-16
|View full text |Cite
|
Sign up to set email alerts
|

Clofazimine Biocrystal Accumulation in Macrophages Upregulates Interleukin 1 Receptor Antagonist Production To Induce a Systemic Anti-Inflammatory State

Abstract: Clofazimine (CFZ) is a poorly soluble antibiotic and anti-inflammatory drug indicated for the treatment of leprosy. In spite of its therapeutic value, CFZ therapy is accompanied by the formation of drug biocrystals that accumulate within resident tissue macrophages, without obvious toxicological manifestations. Therefore, to specifically elucidate the off-target consequences of drug bioaccumulation in macrophages, we compared the level of inflammasome activation in CFZ-accumulating organs (spleen, liver and lu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 34 publications
(49 citation statements)
references
References 59 publications
1
48
0
Order By: Relevance
“…Following eight weeks of sustained therapy with CFZ, the alveolar macrophages are loaded with large amounts of intracellular crystals of the drug, consistent with previous reports from our laboratory [29]. As a result of the accumulation of intracellular drug complexes, intracellular dichroism increased significantly (0.042 ± 0.013, p<0.01, TwoTailed Student's T-Test), revealing that CLDIs are highly organized, self-assembling supramolecular entities, and that the dichroism of these crystals can be detected within a cell.…”
Section: Multi-parameter Live Cell Imaging and Quantification Of Diatsupporting
confidence: 90%
See 1 more Smart Citation
“…Following eight weeks of sustained therapy with CFZ, the alveolar macrophages are loaded with large amounts of intracellular crystals of the drug, consistent with previous reports from our laboratory [29]. As a result of the accumulation of intracellular drug complexes, intracellular dichroism increased significantly (0.042 ± 0.013, p<0.01, TwoTailed Student's T-Test), revealing that CLDIs are highly organized, self-assembling supramolecular entities, and that the dichroism of these crystals can be detected within a cell.…”
Section: Multi-parameter Live Cell Imaging and Quantification Of Diatsupporting
confidence: 90%
“…Based off of previous work, it has been shown that CLDIs tend to be found within tissue macrophages, such as Kupffer cells of the liver, red pulp macrophages of the spleen, and alveolar macrophages within the lung [18,28,29]. Due to the extensive accumulation within alveolar macrophages, these cells were chosen to test this multi-parameter imaging and analysis system in live cells.…”
Section: Multi-parameter Live Cell Imaging and Quantification Of Diatmentioning
confidence: 99%
“…2A, H&E), since CFZ exists in the soluble form. 26 However, between 2 and 4 weeks, CFZ crystalizes in the liver 22,26 and by 4 weeks, small granulomas (Mean±S.D. : 6596±2609 μm 2 ) are apparent (Fig.…”
Section: Resultsmentioning
confidence: 94%
“…2A and C). By 8 weeks, liver CFZ concentration reached its peak 22,26 , which was accompanied by a 2.4-fold increase in total cell number (per field) (Fig. 2C).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation